2006 Kajian reka bentuk kenderaan untuk Jabatan Bomba Dan Penyelamat memadamkan kebakaran hutan jenis Sekunder - Jim, Dylon Walter. (Universiti Malaysia Sarawak (UNIMAS), 2006)
Forest fire can occur at anytime and anywhere without warning. Therefore the Fire Amor Transport (FAT) is especially designed to cope and handle the operation extinguishing forest fire, beside that it is also equipped with the newest and advance technology fire extinguishing tools that can be use at anytime and any fire situation.